Cost reduction study of automotive part using dfa method : car seat - Muhammad, Mohd Noor (2012)
Design for Assembly (DFA) has been widely used in industry and has produced many successes. Some of the methods known in the DFA industry now are the BoothroydDewhurst DFA method, Hitachi Assemblability Evaluation Method (AEM) and the Lucas –Hull DFA method. With these well-known methods, many important changes and developments carried out either manually or through the automatic assembly. The goals of this project are to analyse existing car seat using Boothroyd-Dewhurst DFA and Hitachi Assemblability Evaluation Method (AEM) in terms of assembly time, assembly cost and assembly efficiency. The car seat that has been used in this project is a car seat of Proton Wira. The original car seat has been analysed and showed that Boothroyd-Dewhurst DFA has low percentage design efficiency compare to Hitachi AEM DFA method. The assembly cost of both methods is same. The assembly time of both methods also calculated.